2004
DOI: 10.1104/pp.103.038158
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Interacts with Antifreeze Proteins and Chitinase from Cold-Acclimated Winter Rye

Abstract: During cold acclimation, winter rye (Secale cereale) plants accumulate pathogenesis-related proteins that are also antifreeze proteins (AFPs) because they adsorb onto ice and inhibit its growth. Although they promote winter survival in planta, these dual-function AFPs proteins lose activity when stored at subzero temperatures in vitro, so we examined their stability in solutions containing CaCl2, MgCl2, or NaCl. Antifreeze activity was unaffected by salts before freezing, but decreased after freezing and thawi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 52 publications
1
26
1
1
Order By: Relevance
“…Antifreeze activity has been found in class I and class II chitinases from winter rye (Secale cereale). [31][32][33][34] These classes of chitinases were also induced in salt-adapted cells of tobacco (Nicotiana tabacum) 14) and winged bean (Psophocarpus tetragonolobus).…”
Section: Discussionmentioning
confidence: 99%
“…Antifreeze activity has been found in class I and class II chitinases from winter rye (Secale cereale). [31][32][33][34] These classes of chitinases were also induced in salt-adapted cells of tobacco (Nicotiana tabacum) 14) and winged bean (Psophocarpus tetragonolobus).…”
Section: Discussionmentioning
confidence: 99%
“…condition and the cross talk processes occurring in different stress conditions. Some PRs have been described to be up-regulated under abiotic stress (Tateishi et al, 2001;Stressmann et al, 2004), which suggests the existence of common effectors with biotic stress. The analysis of the expression of PRs and HSP71.2 (for heat shock protein 71.2) in pea plants treated with Cd was carried out by semiquantitative RT-PCR and is shown in Fig.…”
Section: Effects Of CD On Prs and Defense Proteinsmentioning
confidence: 99%
“…An induction of chitinase activity has been observed in pea plants by Cd (Metwally et al, 2003) and other heavy metals like lead and arsenic (Békésiová et al, 2008) and also by osmotic stress (Tateishi et al, 2001), low temperature (Stressmann et al, 2004), and wounding (Wu and Bradford, 2003). Chitinases are probably components of the general defense response program of cells, although they can also play unknown specific roles in heavy metal stress.…”
Section: The Cellular Response To CD Is Mediated By Ja and Etmentioning
confidence: 99%
“…However, BiCHT1 products expressed in both E. coli and bromegrass had chitinase activity but did not affect the growth of ice crystals. Stressmann et al (2004) reported that when winter rye apoplast crude extract containing chitinase/AFP was frozen in the presence of 20 to 200 mM of CaCl 2 , the antifreeze activity was reduced by 30% and was recovered by adding a chelator. This effect was specific to high concentrations (20-200 mM) of CaCl 2 , and antifreeze activity before freeze-thaw cycles was unaffected by the presence of CaCl 2 .…”
Section: Discussionmentioning
confidence: 99%